2013
DOI: 10.1111/jch.12094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intensive Antihypertensive Treatment on Chinese Hypertensive Patients Older Than 70 Years

Abstract: 2This study was performed to investigate whether intensive antihypertensive treatment with achieved blood pressure (BP) 140/90 mm Hg, as compared with standard treatment with achieved BP 150/90 mm Hg, could further improve cardiovascular outcomes in Chinese hypertensive patients older than 70 years. A total of 724 participants were randomly assigned to intensive or standard antihypertensive treatment. After a mean follow-up of 4 years, the mean achieved BP was 135.7/76.2 mm Hg in the intensive treatment grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 29 publications
1
57
0
Order By: Relevance
“…Furthermore, it was reported in this issue of the Journal of Atherosclerosis and Thrombosis that hypertension was the only risk factor significantly associated with stroke incidence in individuals aged ≥ 75 years (old-old) and 60–74 years (young-old) in the Ohasama Study 7) . These results from the observational studies 816) together with findings of previous intervention studies 1720) confirm the appropriateness of the current hypertension guidelines for the management of hypertension for older individuals in Japan 21) ( Table 1 ).…”
supporting
confidence: 78%
“…Furthermore, it was reported in this issue of the Journal of Atherosclerosis and Thrombosis that hypertension was the only risk factor significantly associated with stroke incidence in individuals aged ≥ 75 years (old-old) and 60–74 years (young-old) in the Ohasama Study 7) . These results from the observational studies 816) together with findings of previous intervention studies 1720) confirm the appropriateness of the current hypertension guidelines for the management of hypertension for older individuals in Japan 21) ( Table 1 ).…”
supporting
confidence: 78%
“…31 Wei and colleagues recently showed that treatment to an SBP target of <140 mm Hg using a variety of medications decreased total and cardiovascular mortality by 41.7% and 50.4%, respectively, in a population of Chinese patients >70 years. 32 Other recent results reported by the China Stroke Primary Prevention Trial suggest that addition of folic acid to antihypertensive treatment may afford further reduction in risk for stroke. 33 Clinical trials have shown clear benefits to any antihypertensive treatment.…”
Section: T R E a T M E N T A N D C O N T R O L O F H Y P E R T E N S mentioning
confidence: 97%
“…There were no significant differences in CV events between the treatment groups in subgroup analyses of the Candesartan Antihypertensive Survival Evaluation in Japan (CASE-J) [26], the Combination therapy of hypertension to Prevent cardiovascular Events (COPE) [27] and Intervention as a Goal in Hypertension (INSIGHT) [28] and Valsartan Antihypertensive Long-term Use Evaluation (VALUE) [29], as well as in the Japanese Trial to Assess Optimal Systolic blood pressure (JATOS) [30], SCOPE [21], STOP-H2 [31] and Valsartan in elderly Isolated Systolic Hypertension (VALISH) studies [32] as a main outcome of these trials. In addition, a significant reduction in heart failure was demonstrated in subgroup analyses of the ALLHAT [33], SHEP [34] and VALUE [29] studies, and as a secondary outcome in PROBE [20]. However, there was a significant increase in heart failure in those assigned to doxazosin compared to the chlorthalidone group in ALLHAT [23].…”
Section: Cardiovascular Benefits Of Antihypertensive Medicationsmentioning
confidence: 99%
“…At least five RCTs have demonstrated that antihypertensive drugs decrease all-cause mortality in hypertensive elderly patients. The reduction in allcause mortality was a primary outcome in the trial by Wing et al [25] and a secondary outcome in the HYVET [5], PROBE [20], STOP-H [17] and INSIGHT [28] studies. By contrast, the results of other trials have indicated no significant difference in all-cause mortality amongst treatment groups in the elderly [14,16,18,19,21,23,35].…”
Section: Cardiovascular Benefits Of Antihypertensive Medicationsmentioning
confidence: 99%